Strategi Pemasaran Produk Fulprotek PT Asuransi Takaful Keluarga dan Bank Muamalat Indonesia - Putri Ayuni; Nuri Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
Marketing is one of the economic sciences that has been developing for a long time, and until now marketing greatly affects the success of a company to be able to survive in market share. Therefore the company must carry out a marketing mix which also has an influence to determine the success or failure of marketing its products. If the marketing mix implemented by the company is able to market its products well, this will affect the company's goals. Keywords: Marketing. Economy, Fullprotect